2021
DOI: 10.1186/s13071-021-04971-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the Anopheles hyrcanus group (Diptera: Culicidae) based on rDNA–ITS2 and mtDNA–COII

Abstract: Background The Anopheles hyrcanus group, which includes 25 species, is widely distributed in the Oriental and Palaearctic regions. Given the difficulty in identifying cryptic or sibling species based on their morphological characteristics, molecular identification is regarded as an important complementary approach to traditional morphological taxonomy. The aim of this study was to reconstruct the phylogeny of the Hyrcanus group using DNA barcoding markers in order to determine the phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The comparison of intra- and interspecific ITS2/ COII variation in the present study revealed that ITS2 may be a more effective marker for differentiating species than COII , which is consistent with previous findings that an effective DNA marker should have a small intraspecific distance and a large interspecific distance [ 109 ]. The major downside of using COII for phylogenetic analysis is that COII may be unable to distinguish between closely related species [ 110 ]. Thus, additional research in the Cambodia–Laos border using nuclear and mtDNA sequencing is necessary to accurately identify species.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of intra- and interspecific ITS2/ COII variation in the present study revealed that ITS2 may be a more effective marker for differentiating species than COII , which is consistent with previous findings that an effective DNA marker should have a small intraspecific distance and a large interspecific distance [ 109 ]. The major downside of using COII for phylogenetic analysis is that COII may be unable to distinguish between closely related species [ 110 ]. Thus, additional research in the Cambodia–Laos border using nuclear and mtDNA sequencing is necessary to accurately identify species.…”
Section: Discussionmentioning
confidence: 99%
“…Using overnight trapping with battery-operated Centers for Disease Control and Prevention (CDC) light traps (model 1012, John W. Hock Inc., USA) in cattle/pig pens or human rooms from 8:00 pm to 8:00 am, adult mosquitoes were collected in Pathoomphone County (Champasak Province) in 2017, as well as in Pak lay County (Xayabuli Province) and Yot Ou County (Phongsaly Province) in 2019 in accordance with our previous study [ 33 ]. The live adult mosquitoes were killed by freezing in a refrigerator.…”
Section: Methodsmentioning
confidence: 63%
“…The extraction of genomic DNA in individual mosquitoes was carried out following the manufacturer’s instructions (QIAamp ® DNA Mini Kit, Germany). The amplification for approximately 650 bp of the COII gene was carried out using primers LEU-F (5′-TCTAATATGGCAGATTAGTGCA-3′) and LYS-R (5′-ACTTGCTTTCAGTCATCTAATG-3′) [ 33 ]; a fragment containing codon 1014 of the An. sinensis vgsc gene (325-bp polymerase chain reaction [PCR] product of the kdr gene) was amplified using primers KDR-F (5′-TGCCACTCCGTGTGTTTAGA-3′) and KDR-R (5′-GAGCGATGATGATCCGAAAT-3′) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fang et al studied the phylogenetic relationships of 18 species of the Hyrcanus group based on COI sequences [47]. Zhang et al compared ITS2 and COII fragments in constructing phylogenetic trees and suggested that ITS2 sequences could be a better molecular marker to distinguish closely related mosquito species [48]. However, the lengths of ITS2 sequence fragments are different, and thus it is difficult to compare them in the reconstruction of phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 99%